The Factors Related to the Use of the IUD at Health Center of Batu-batu, Soppeng Regency in 2019 - Nurul Fatwa S; Rauly Rahmadhani; Arlina Wiyata Gama (PT FORMOSA CENDEKIA GLOBAL, 2023)
Currently, the problem that is being faced by the Indonesian state is the population problem. The IUD (Intrauterine Contraception) is a long-term contraceptive option, but most women prefer short-term contraception such as pills, injections and implants. This research is a descriptive survey with a cross sectional study design. The sample of this study were women of childbearing age who were married and used contraception in the working area of ​​the Batu-Batu Health Center, Marioriawa District, Soppeng Regency from January to October 2019 and a total of 2017 people. The aim of the study: to determine the factors associated with the use of the IUD in women of childbearing age as a long-term contraceptive method in the working area of ​​the Batu-Batu Health Center, Soppeng Regency. The results of the study: and mother culture. Conclusion: there is a significant relationship between attitude, mother's occupation and husband's support and experience of contraception towards IUD use in women of childbearing age, while the level of age, level of education, level of knowledge, parity and mother's culture do not have a significant relationship